The encyclopedia of nutrition and good health - Ronzio, Robert A. (Checkmark Books, 2003)
Alphabetical listings cover such nutritional topics as vitamins, carbohydrates, processed foods, eating disorders, food allergies, and diseases and health problems related to nutrition.